PENGARUH CURRENT RATIO (CR) DAN DEBT TO ASSETS RATIO (DAR)TERHADAP RETURN ON ASSETS (ROA) PADA PT HUTAMA KARYA (PERSERO) PERIODE 2014-2024 - Dino Satria Ranggana; Ayu Puspa Lestiyadi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to determine the effect of the Current Ratio (CR) and Debt to Assets Ratio (DAR) variables, both partially and simultaneously on the Return on Assets (ROA) of PT Hutama Karya (Persero) for the 2014-2024 period. The research method used in this study is a quantitative method with a descriptive approach. The selected population is the financial statements of PT, Hutama Karya with the sample used being the financial statements in the form of balance sheets and profit and loss statements for the 2014-2024 period. The data was obtained from the website https://www.hutamakarya.com Based on the research results obtained, that partially the Current Ratio (CR) variable has an influence and is significant on Return on Assets (ROA). The results of the study are proven by the significance value (0.032 <0.05) and t count (2.588)> t table (1.859) and the Debt to Assets Ratio (DAR) variable has an influence and is significant on Return on Assets (ROA). The results of the study are proven by the significance value (0.020 < 0.05) and tcount (2.881) > ttable (1.859). While simultaneously there is no significant influence between the variables Current Ratio (CR) and Debt to Assets Ratio (DAR) on the Return on Assets (ROA) variable. The results of the study are proven by the significance value (0.056 > 0.05) and the value of fcount < fttable, namely (4.222) < (4.459). R-Square in the regression model is 0.392 or 39.2%. While the remaining 60.8% is influenced by other factors not included in the regression model. Keywords: Current Ratio, Debt to Assets Ratio and Return on Assets